A importância da obra de Solano Trindade no panorama da literatura brasileira: uma reflexão sobre o processo de seleção e exclusão canônicas - Santos, Suely Maria Bispo dos (2012)
This research investigates the silence and lack of acknowledgement surrounding the name and work of Solano Trindade, one of the pioneers and most important representatives of Afro-Brazilian literature. The discussions on the appearance of Black literature in Brazil, stemming from the need to give voice and visibility to the many writers ignored by dominating sectors, are relevant issues identified and analyzed throughout this study. The present project not only aims to better understand and perceive the life and work of Solano Trindade, but also reflects on the process of selection and exclusion of diverse social, ethnic and sexual groups defined by the literary canon.